ChemInform Abstract: A Robust and Modular Synthesis of Ynamides. Issue 28 (25th June 2015) - Mansfield, Steven J.; Campbell, Craig D.; Jones, Michael W.; Anderson, Edward A.
Abstract The method for the synthesis of the title compounds uses trichloroethene as an inexpensive two carbon synthon and overcomes many of the limitations of other approaches.